Optimization of flocculation process for a new myco-coagulant to reduce water turbidity - Jebun, Nessa; Al-Mamun, Abdullah; Alam, Md. Zahangir; Ahmad Raus, Raha (2016)
The flocculation process to reduce turbidity from kaolin suspension by a new myco-coagulant was optimized. The results indicated that turbidity removal of 94% (from 650 NTU to 38 NTU within 5 minutes settling time) was achieved by a combination of rapid and slow mixing process. A sequential optimization strategy based on a statistical experimental design was used to determine the suitable rapid and slow mixing speed and time. Four process parameters were optimized by the response surface methodology (RSM), based on the face-centered central composite design (FCCCD). The optimum agitation speed and mixing time were found as 250 rpm & 7 mins for rapid mixing stage; and as 90 rpm & 22 minutes for slow mixing stage, respectively. Analysis of variance (ANOVA) showed a good regression coefficient (R2) of 0.95, which indicated a satisfactory fit of the model data with the experimental results. The findings were statistically significant at p<0.05.